The Impact of Brand Authenticity, Brand Experience, and Self-Congruity Toward Brand Loyalty as Mediated by Brand Love: A Case of Apple Inc. - Michael Gunawan; Vincenzio Evan Siemon (iBuss Management, 2020)
As the global marketplace faces fiercer competition and changing consumer demands, the notion of branding as a competitive advantage has never been more relevant. One recent notable case is found in Apple Inc., a leading global technological corporation with a stock market value matching one-third of the UK’s economy. Despite having long been the world’s number one company in brand value, Apple has shown signs of decline with its weakening profits due to a brand loyalty crisis. Such a case brings the researchers’ attention into exploring and synthesizing existing understandings of brand loyalty, which resulted in the creation of a new marketing model intended for aiding the sales of brand-focused companies. This research inspects the importance of brand love, a concept which is still largely unexplored, as a mediating variable for brand loyalty and its antecedents: brand authenticity, brand experience, and self-congruity. Data were collected using a self-administered questionnaire with a sample of 106 Apple users living in Surabaya, Indonesia, one of the world’s most important markets for Apple, and processed using bootstrapping. Results show that brand authenticity, brand experience, and self-congruity directly affect brand loyalty, and brand love partially mediates the effect of brand authenticity toward brand loyalty.Keywords: Brand Loyalty, Brand Authenticity, Brand Experience, Self-congruity,Brand Love